(untitled) (Boletín Semillero de Investigación en Familia, 2021)
Introduction: Humanitarian crises are caused by different climatic, social, political, cultural and health factors, which drastically modify the life of the population and its different contexts, generating mental, neurological and substance-related problems. Objective: Design and execute a communication campaign for mental health to face the impact generated by COVID-19 and support for future humanitarian crisis situations. Materials and methods: Focused and collective group interventions based on the thematic content of the Virtual Course - Humanitarian mhGAP - COVID-19 of the Virtual Campus of Public Health of the Pan American Health Organization. Results: 5 interventions were performed; 4 group interventions and 1 Stand for induced demand, to 101 nursing students and 190 students from other disciplines at the San Antonio campus of the Universidad de los Llanos. Conclusions: The active participation of the participants in the interventions carried out was positive, in addition, the application of the pre and post test allowed to demonstrate the positive impact in terms of the level of knowledge and perception of the topics addressed in the people intervened.